N6-(2-Hydroxyethyl) Adenosine From Cordyceps cicadae Ameliorates Renal Interstitial Fibrosis and Prevents Inflammation via TGF-β1/Smad and NF-κB Signaling Pathway - Zheng, Rong; Zhu, Rong; Li, Xueling; Li, Xiaoyun; Shen, Lianli; Chen, Yi; Zhong, Yifei; Deng, Yueyi (Frontiers in Physiology, 2018)
Renal interstitial fibrosis is characterized by inflammation and an excessive accumulation of extracellular matrix, which leads to end-stage renal failure. Our previous studies have shown that a natural product from Cordyceps cicadae can ameliorate chronic kidney diseases. N6-(2-Hydroxyethyl) adenosine (HEA), a physiologically active compound in C. cicadae, has been identified as a Ca2+ antagonist and an anti-inflammatory agent in pharmacological tests. However, its role in renal interstitial fibrosis and the underlying mechanism remains unclear. Here, unilateral ureteral obstruction (UUO) was used to induce renal interstitial fibrosis in male C57BL/6 mice. Different doses of HEA (2.5, 5 and 7.5 mg/kg) were given by intraperitoneal injection 24 h before UUO, and the treatment was continued for 14 days postoperatively. Histologic changes were examined by hematoxylin & eosin, Masson’s trichrome, and picrosirius red stain. Quantitative real-time PCR analysis, enzyme-linked immunosorbent assays, immunohistochemistry and western blot analysis were used to evaluate proteins levels. And the results showed that HEA significantly decreased UUO-induced renal tubular injury and fibrosis. In vivo, HEA apparently decreased UUO-induced inflammation and renal fibroblast activation by suppression of the NF-κB and TGF-β1/Smad signaling pathway. In vitro, HEA also obviously decreased lipopolysaccharide-induced inflammatory cytokine level in RAW 264.7 cells and TGF-β1-induced fibroblast activation in NRK-49F cells by modulating NF-κB and TGF-β1/Smad signaling. In general, our findings indicate that HEA has a beneficial effect on UUO-induced tubulointerstitial fibrosis by suppression of inflammatory and renal fibroblast activation, which may be a potential therapy in chronic conditions such as renal interstitial fibrosis.